2014
DOI: 10.1111/pde.12345
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Nevus Comedonicus Involving the Palm: Questionable Role of the Pilosebaceous Unit in Pathogenesis

Abstract: A 10-year-old boy had multiple grouped pits with black plugs arranged along the lines of Blaschko on his left chest, arm, and palm. Involvement of the palms is rarely reported in the literature. Recent reports have described mosaic acneiform conditions that could share pathogenetic mechanisms with nevus comedonicus. We briefly review the literature on mosaic conditions with acneiform lesions including nevus comedonicus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Linear or blaschkoid presentations involving the face, neck, upper extremities, and trunk are most common, with a prevalence of 1 in 45 000 to 1 in 100 000 persons . However, palmar-plantar presentations have been described despite these areas being devoid of pilosebaceous units . Nevus comedonicus development is postulated to reflect abnormal filaggrin expression or overstimulation of fibroblast growth factor receptor 2, with high expression of interleukin 1 leading to improper pilosebaceous unit development .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear or blaschkoid presentations involving the face, neck, upper extremities, and trunk are most common, with a prevalence of 1 in 45 000 to 1 in 100 000 persons . However, palmar-plantar presentations have been described despite these areas being devoid of pilosebaceous units . Nevus comedonicus development is postulated to reflect abnormal filaggrin expression or overstimulation of fibroblast growth factor receptor 2, with high expression of interleukin 1 leading to improper pilosebaceous unit development .…”
Section: Discussionmentioning
confidence: 99%
“…2 However, palmar-plantar presentations have been described despite these areas being devoid of pilosebaceous units. 3,4 Nevus comedonicus development is postulated to reflect abnormal filaggrin expression or overstimulation of fibroblast growth factor receptor 2, with high expression of interleukin 1 leading to improper pilosebaceous unit development. 2 However, there is still debate as to whether development of nevus comedonicus, particularly on the palms and soles where pilosebaceous units are absent, may be caused by abnormal epidermal invagination.…”
mentioning
confidence: 99%
“…Histologically, NC is characterized by dilated invaginations of underdeveloped hair follicles filled with cornified debris and devoid of hair shafts . However, studies have reported extensive NC involving the palms, indicating that the pathophysiology of the condition could involve more than just the pilosebaceous unit …”
Section: Discussionmentioning
confidence: 99%
“…3 However, studies have reported extensive NC involving the palms, indicating that the pathophysiology of the condition could involve more than just the pilosebaceous unit. 4 The molecular basis of NC is still unknown. Fibroblast growth factor receptor 2 mutations have been noted in some cases, but according to recent evidence, these mutations are not related to the pathophysiology of NC.…”
Section: Discussionmentioning
confidence: 99%